Brachial plexus injury: the problems of expectant management! - Thapa, Amit (Nepal Journal of Neuroscience, 2024)
Brachial plexus injury is a devastating injury, affecting primarily young people involved in bike accidents. The management of these often conservatively cared patients has transformed over the last decades with the improvisation in diagnostic modalities, refinement in surgical approaches and availability of newer surgical adjuncts. Patients after surgical treatment, can lead productive life as they become able to use their paralyzed limb. They should no longer be doomed to expectant management, where their recovery is left to chance. However, it is imperative to recognize surgical indications at the earliest and offer appropriate surgical care to achieve the best possible outcome. If in doubt, it is recommended to refer these patients to centers dealing with care of these patients to avoid delays